2000
DOI: 10.1161/01.atv.20.2.575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Individual Plasma Lipoprotein(a) Variations In Vivo on Its Competition With Plasminogen for Fibrin and Cell Binding

Abstract: Abstract-Simultaneous natural changes in lipoprotein(a) [Lp(a)] and plasminogen occur in the nephrotic syndrome and offer a unique opportunity to investigate their effects on plasminogen activation under conditions fashioned in vivo. Plasminogen, Lp(a), and apolipoprotein(a) in plasma were characterized, and their competitive binding to carboxyterminal lysine residues of fibrin and cell membrane proteins was determined in nephrotic children during a flare-up of the disease (61 cases) and after 6 weeks (33 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 68 publications
0
25
0
3
Order By: Relevance
“…32 Briefly, plasma was supplemented with protease inhibitors and incubated with varying concentrations of mAb A10.2. The samples were then incubated (50 L per well) with fibrin for 1 hour at 37°C; the plates were washed and probed with a polyclonal antibody directed against apo(a).…”
Section: Inhibition Of the Fibrin-binding Function Of R-apo(a) And Lpmentioning
confidence: 99%
“…32 Briefly, plasma was supplemented with protease inhibitors and incubated with varying concentrations of mAb A10.2. The samples were then incubated (50 L per well) with fibrin for 1 hour at 37°C; the plates were washed and probed with a polyclonal antibody directed against apo(a).…”
Section: Inhibition Of the Fibrin-binding Function Of R-apo(a) And Lpmentioning
confidence: 99%
“…Apo(a) has a high affinity for lysine-binding sites on fibrin(ogen) 9,10 and may therefore compete with plasminogen at sites of fibrin deposition and thus interfere with the fibrinolytic system. 11 In the same line apo(a), or fragments of apo(a) that have been found in human plasma and urine, 12 may antagonize the effect of angiostatin, a biologically active fragment of plasminogen that inhibits angiogenesis. 13,14 Finally, Lp(a) may contribute to lipid delivery to atherosclerotic plaques.…”
mentioning
confidence: 99%
“…The subsequent appearance of plasminogen derivatives and the binding of mAbs or Fab was determined as the fibrin was degraded. This experimental setup was similar to the one previously described to isolate the effect of Lp(a) on plasminogen activation [13], and offered the additional advantage to measure plasmin(ogen) and monoclonal antibodies on the same surface of fibrin using specific antibodies and a chromogenic substrate assay. As for plasminogen binding, the ability of mAbs to enhance plasmin formation was concentration dependent until a maximum was reached.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the lipoprotein Lp(a) [10], a highly atherogenic lipoprotein particle, which possesses multiple copies of plasminogen-like kringle 4 in its apolipoprotein(a), apo(a), moiety [11]. Lp(a) inhibits plasmin formation by competing with plasminogen for binding sites on fibrin and cell surfaces [12,13]. On the other hand, it has been demonstrated that the interaction of monoclonal antibodies with the low-or high-affinity LBSs of plasminogen may result in conformational changes yielding the plasminogen more susceptible to activation by plasminogen activators [14,15].…”
Section: Introductionmentioning
confidence: 99%